2002
DOI: 10.1044/1092-4388(2002/088)
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Stuttering in the Community Across the Entire Life Span

Abstract: A randomized and stratified investigation was conducted into the epidemiology of stuttering in the community across the entire life span. Persons from households in the state of New South Wales, Australia, were asked to participate in a telephone interview. Consenting persons were given a brief introduction to the research, and details were requested concerning the number and age of the persons living in the household at the time of the interview. Interviewees were then given a description of stuttering. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
147
6
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 275 publications
(197 citation statements)
references
References 18 publications
21
147
6
7
Order By: Relevance
“…The ratio was nearly four males to one female. This finding corresponds with epidemiological study of Craig and colleagues (2002) done in New South Wales that mentioned the ratio of males to females between 2/1 and 4/1 (39). In another study conducted by Craig et al (2009) ratio was 3 males to 1 female (14).…”
Section: Resultssupporting
confidence: 75%
“…The ratio was nearly four males to one female. This finding corresponds with epidemiological study of Craig and colleagues (2002) done in New South Wales that mentioned the ratio of males to females between 2/1 and 4/1 (39). In another study conducted by Craig et al (2009) ratio was 3 males to 1 female (14).…”
Section: Resultssupporting
confidence: 75%
“…However, a recent longitudinal study looking at development of early language by Reilly et al (2009) showed that 85% of parents gave accurate reports of their children stuttering at 3 years old, and it seems likely that parents of 16-year-olds would have an even more accurate perception of their child's speech. Furthermore, the male to female ratio (4:1) of participants who were reported to stutter within this study is consistent with other research for adolescence and adulthood (Bloodstein, 1995;Craig, Hancock, Tran, Craig, & Peters, 2002). On a related note, it would have been desirable to check whether participants were still stuttering at the later ages sampled in this study, but these data were not collected.…”
Section: Discussionsupporting
confidence: 69%
“…The order of presentation for the two persons was randomized. The target person was described as male because males are much more likely to stutter than females (Craig, Hancock, Tran, Craig, & Peters, 2002). A second group of participants was asked to rate only the personality of a typical adult male, with no mention at all of stuttering.…”
Section: Methodsmentioning
confidence: 99%